The calcium–frequency response in the rat ventricular myocyte: an experimental and modelling study. (26th June 2016) - Gattoni, Sara; Røe, Åsmund Treu; Frisk, Michael; Louch, William E.; Niederer, Steven A.; Smith, Nicolas P.
Abstract : Key points: In the majority of species, including humans, increased heart rate increases cardiac contractility. This change is known as the force–frequency response (FFR). The majority of mammals have a positive force–frequency relationship (FFR). In rat the FFR is controversial. We derive a species‐ and temperature‐specific data‐driven model of the rat ventricular myocyte. As a measure of the FFR, we test the effects of changes in frequency and extracellular calcium on the calcium–frequency response (CFR) in our model and three altered models. The results show a biphasic peak calcium–frequency response, due to biphasic behaviour of the ryanodine receptor and the combined effect of the rapid calmodulin buffer and the frequency‐dependent increase in diastolic calcium. Alterations to the model reveal that inclusion of Ca 2+ /calmodulin‐dependent protein kinase II (CAMKII)‐mediated L‐type channel and transient outward K + current activity enhances the positive magnitude calcium–frequency response, and the absence of CAMKII‐mediated increase in activity of the sarco/endoplasmic reticulum Ca 2+ ‐ATPase induces a negative magnitude calcium–frequency response. Abstract: An increase in heart rate affects the strength of cardiac contraction by altering the Ca 2+ transient as a response to physiological demands. This is described by the force–frequency response (FFR), a change in developed force with pacing frequency. The majority of mammals, including humans, have a positive FFR, and cardiac contraction strength increases with heart rate. However, the rat and mouse are exceptions, with the majority of studies reporting a negative FFR, while others report either a biphasic or a positive FFR. Understanding the differences in the FFR between humans and rats is fundamental to interpreting rat‐based experimental findings in the context of human physiology. We have developed a novel model of rat ventricular electrophysiology and calcium dynamics, derived predominantly from experimental data recorded under physiological conditions. As a measure of FFR, we tested the effects of changes in stimulation frequency and extracellular calcium concentration on the simulated Ca 2+ transient characteristics and showed a biphasic peak calcium–frequency relationship, consistent with recent observations of a shift from negative to positive FFR when approaching the rat physiological frequency range. We tested the hypotheses that (1) inhibition of Ca 2+ /calmodulin‐dependent protein kinase II (CAMKII)‐mediated increase in sarco/endoplasmic reticulum Ca 2+ ‐ATPase (SERCA) activity, (2) CAMKII modulation of SERCA, L‐type channel and transient outward K + current activity and (3) Na + /K + pump dynamics play a significant role in the rat FFR. The results reveal a major role for CAMKII modulation of SERCA in the peak Ca 2+ –frequency response, driven most significantly by the cytosolic calcium buffering system and changes in diastolic Ca 2+ . Key points: In the majority of species, including humans, increased heart rate increases cardiac contractility. This change is known as the force–frequency response (FFR). The majority of mammals have a positive force–frequency relationship (FFR). In rat the FFR is controversial. We derive a species‐ and temperature‐specific data‐driven model of the rat ventricular myocyte. As a measure of the FFR, we test the effects of changes in frequency and extracellular calcium on the calcium–frequency response (CFR) in our model and three altered models. The results show a biphasic peak calcium–frequency response, due to biphasic behaviour of the ryanodine receptor and the combined effect of the rapid calmodulin buffer and the frequency‐dependent increase in diastolic calcium. Alterations to the model reveal that inclusion of Ca 2+ /calmodulin‐dependent protein kinase II (CAMKII)‐mediated L‐type channel and transient outward K + current activity enhances the positive magnitude calcium–frequency response, and the absence of CAMKII‐mediated increase in activity of the sarco/endoplasmic reticulum Ca 2+ ‐ATPase induces a negative magnitude calcium–frequency response.